PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM MEMANFAATKAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DI SMA NEGERI 7 DENPASAR - Cokorda Gede Anom Wiratmaja (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
Pedagogic competence is the ability to manage learning, design, implementation of learning, evaluation of learning outcomes, and development of students to actualize their various potentials. The purpose of this study was to analyze and describe the pedagogic competence of teachers in designing ICT-based learning media, producing ICT-based learning media, and using ICT-based learning media. The research subjects were teachers of SMA Negeri 7 Denpasar in the academic year 2021/2022. The object of research is the use of ICT-based learning media. The method used in this research is descriptive method, using the percentage technique to see the increase that occurs from cycle to cycle. The action research was carried out in two cycles and each cycle carried out four activities, namely CAR planning, action, observation, and reflection. The results of the study show (1) the pedagogic competence of teachers in designing learning media is included in the good category with a percentage of 78%. In terms of designing learning media, the competence that the teacher has on average is in the very good category. (2) The teacher's pedagogic competence in producing learning media is included in the good category with a percentage of 80%. (3) The pedagogic competence of teachers in the use of learning media is included in the good category with a percentage of 83%. The use of ICT-based learning media in explaining subject matter can make abstract learning seem real through videos and pictures.